Analisis Spasial Sebaran dan Kerapatan Mangrove di Kawasan Pesisir Pantai Serdang Bedagai Sumatera Utara - Ardiansyah, Dede; Widiyanto, Widiyanto; Wihadanto, Ake (Universitas Batanghari Jambi, 2025)
This research aims to obtain a map of the distribution and density of mangroves, analyze the level of ecosystem sustainability, including ecological, economic, and social dimensions, in the mangrove area, and determine priority strategies for the sustainability of the mangrove ecosystem in five sub-districts of Serdang Bedagai Regency. This research began with collecting primary and secondary data through direct observation, interviews with the community, and a literature study. The results of this research show that there is an increase in the area of mangroves on the coast of the Serdang Bedagai Regency area of 3.48 ha. From image data analysis in 2020, the area of mangroves was 1,037.37 ha, and in 2022, the area of mangroves was 1,040.85 ha. There is also an increase in the area of mangroves in the categories of very dense (373.86 ha), very rare (3.89 ha), and there is a decrease in mangrove area in the dense category (201.29 ha) and rare category (172.98 ha). amounting to 172.98 ha (17%) with rarely changing conditions. By looking at this data, it can be said that the sustainability of mangrove forests is good. The priority strategy implemented is community outreach about the importance of mangrove ecosystems and environmental management. Preserving mangroves is essential due to their vital role in maintaining ecosystem balance.